O imperativo do gozo na sociedade de consumo - Macedo, Fernanda Toledo (2013)
This research analyzes the elements of the discourse of the magazine NEW / Cosmopolitan. The analysis focuses on the participation of the superego in the statements of the magazine , considering how this instance of the psychic apparatus , which is articulated in conjunction with the feelings of drive (mostly death ) and " Rules" relentless search for pleasure - agreed by Lacan as an imperative jouissance - is present in contemporary society, orchestrating various discourses of consumption, where the slogan is " be happy " and " consume " . We examined the construction of statements of publication, targeted for the theme of happiness (directly or indirectly ) within the parameters of Positive Psychology . The aim was to study how the text is constructed to not only entice readers , but to order and direct the enjoyment through consumption. The corpus consists of the issues from January 2005 to April 2013 of the magazine. The methodology used in the analysis is qualitative , exploratory and descriptive confronting theories about the consumer society , the construction of the individual in this picture and thinking how their fragmentation can influence the meaning of goods, made possible from the discourse of Positive Psychology . The authors underlying the study are : João Freire Filho , Algirdas J. Greimas , Sigmund Freud, Gilles Lipovetsky , Zymunt Bauman , Michel Foucault and Guy Debord , among others . The main concepts in the development of the research are : happiness, the imperative of enjoyment in the society of the spectacle and consumption, being articulated in a way that allow performing reflections about the identity of the brand NEW / Cosmopolitan as an authority recognized by your target audience, placed the role of holding the " know" that leads the reader to happiness ( and enjoyment ) . The starting point is the ephemeral nature of postmodern society as a basis for the construction of this editorial product as discursive device